Foreign Migrant Illegal Trespassing In Sabah Forest: The Need For Legal Awareness - Intung, Rovina; Rahim, Rohani Abdul; Landa, Azizah; Makanah, Herlina; Tajuddin, Muhammad Afiq Ahmad; Bakar, Kamarudin Abu (Universiti Sains Malaysia, 2016)

(untitled)
Sabah is one of the states in Malaysia, which have gazetted forests reserves with a total area of 3.6 million hectares. The forestry sector through its timber revenue has acquired the annual tax collection amounted to millions of ringgit. This economic sector is one of the main contributors to Sabah state revenue. Sabah forest is rich in forest products as well as the flora and fauna are constantly maintained and monitored by the Forestry Department of Sabah from any trespassing activity. However, there are still attempts by foreign migrants to intrude the forest illegally to acquire forest products, especially in the forest reserves and violate the existing legislation. This paper aims to discuss the causes of the invasion of forest reserves by foreign migrants, the offenses committed by foreign migrant activities in the forest reserves, violation of specific legislation such as the Immigration Act 1959/63 and the Forest Enactment 1968. Finally, to propose adequate measures to create awareness among various interested groups and local communities and to always be responsible for preserving and protecting the forests from illegal trespassing by the foreign migrants.